Economic investment in health programs in North, Central and South American countries during the last twenty years - Restrepo-Betancur, Luis F (Universidad y Salud, 2023)
<span class="NormalTextRun SCXW98584843 BCX0" data-ccp-parastyle="Resumen" data-ccp-parastyle-defn="{"ObjectId":"61d23850-0b3a-4472-89a1-e4129747fb02|93","ClassId":1073872969,"Properties":[469775450,"Resumen",201340122,"2",134234082,"true",134233614,"true",469778129,"Resumen",335572020,"1",469777841,"Cambria",469777842,"Times New Roman",469777843,"MS Mincho",469777844,"Cambria",469769226,"Cambria,Times New Roman,MS Mincho",335551500,"4278190080",335557856,"4278190080",268442635,"19",335551547,"13322",335559740,"240",201341983,"0",335559739,"180",335551550,"6",335551620,"6",469778324,"Normal"]}">Introduction: Health investment is essential to provide patient care and develop prevention programs for the wellbeing of citizens. Objective: To compare investment in health programs by American countries during the last twenty years. Methods: A General Linear Model based on the MANOVA technique was applied, which was supplemented with cluster analysis. The assessed variables were: investments in health by the public sector (expressed as a percentage); percentage of the total spending invested in health; and health GDP (Gross Domestic Product) and public health expenditure per capita (presented in Euros). Results: In reference to GDP and public spending per capita allocated to health (in Euros), the United States shows a statistically significant difference compared to other nations of the continents (p<0.05). Venezuela has the lowest public expenditure in health, expressed as percentage. Conclusions: There is a large difference in terms of investment in health in the Americas, where the economically strongest countries such as the United States and Canada show the highest figures. Venezuela is the country with the lowest GDP investment in health, being the only nation that reduced this variable in recent years.